RESISTENSI TERHADAP DELEGITIMASI KEKUASAAN ORDE BARU DALAM ANTOLOGI PUISI NYANYIAN AKAR RUMPUT KARYA WIJI THUKUL - Achmad Naufal Irsyadi; Novi Anoegrajekti; Dina Dyah Kusumayanti (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2019)
This study observed the form and mechanism of power of the New Order in Wiji Thukul’s poem to discover theoretical and factual novelty. This study applied sociology of literature as an approach to gain a strengthening basis about the relationship between Wiji Thukul’s poem and social context during the New Order. The theory of Power by Michel Foucault was used to overview and highlight the form and mechanism of power of The New Order, so that the model of the analysis was analytical descriptive. The object of this study was the antology of Wiji Thukul’s poem Nyanyian Akar Rumput. Based on the analysis, there found that the New Order was an authoritative, repressive, and oppressive government. His power performed through the relation of power and dominant discourse that were spread and legitimated through power networking established by the New Order. This characteristics of power had made Wiji Thukul consistently sacrificed and struggled to conduct a resistance by media of poem. From this study, there could be concluded that Wiji Thukul’s poem was fully loaded with intense and dominant sociological outlook.